Answer :

Hrishii

Answer:

[tex] a = \boxed{3 }\: \: b = \boxed{6} \: \: c = \boxed{5}[/tex]

Step-by-step explanation:

[tex] {3}^{ \frac{6}{5} } \\ = \sqrt[5]{ {3}^{6} } \\ equating \: it \: with \\ \sqrt[c]{ {a}^{b} } \: we \: find \\ a = \boxed{3 }\: \: b = \boxed{6} \: \: c = \boxed{5}[/tex]

Step-by-step explanation:

Step-by-step explanation:

\begin{lgathered}{3}^{ \frac{6}{5} } \\ = \sqrt[5]{ {3}^{6} } \\ equating \: it \: with \\ \sqrt[c]{ {a}^{b} } \: we \: find \\ a = \boxed{3 }\: \: b = \boxed{6} \: \: c = \boxed{5}\end{lgathered}

3

5

6

=

5

3

6

equatingitwith

c

a

b

wefind

a=

3

b=

6

c=

5

Other Questions